Electron Scattering Experiments: Gas Phase Reactions Involving Free Electrons - Michael Allan (CHIMIA)
The electron scattering field and its implications for both basic scientific knowledge and practical applications are briefly introduced. A preliminary account of a new experiment within this field, a crossed beam study of the O-/diatomic molecule reaction is then given. It was found that the studied molecules fall into two distinct classes with respect to associative electron detachment. In the first class, represented by O-/CO and O-/H2 the liberated bond energy is transferred almost exclusively into the vibrational motion of the product molecule. In contrast, in the O-/NO system a large fraction of the energy is given to the departing free electron.